Biancaea scabrida, a new species of the Caesalpinia group (Fabaceae) from Peninsular Malaysia - Choo, Le Min (Phytotaxa, 2021)
The new species Biancaea scabrida, currently only known from Peninsular Malaysia, is described and illustrated. The new species most resembles B. parviflora and B. oppositifolia in its inflorescence, but can be distinguished from both species by its sepals which have short stiff scabrid hairs, and its pistil which has stiff and hispid hairs. It also has alternately arranged leaves and inflorescence branches, a lack of a persistent suborbicular stipule, few pinnae per rachis (2–6 pairs) and relatively fewer leaflets per pinna ((3–)5–9 pairs). A provisional IUCN conservation assessment and a taxonomic key to Biancaea is also provided here.